Neoschizaea, a new grass-fern genus segregated from Schizaea (Schizaeaceae) - Silva, D. Victor Souza E; Santiago, Augusto César Pessôa; Almeida, Thaís Elias (Phytotaxa, 2026)
Schizaeaceae is a fern family with fossil records dating to the Early Cretaceous and currently comprise approximately 40 species. Although recent phylogenomic studies have revalidated Microschizaea to resolve paraphyly issues within the family, the genus Schizaea remains non-monophyletic due to the isolated phylogenetic position of the S. pusilla clade. To restore its monophyly, we describe a new genus, Neoschizaea. Our taxonomic conclusions are supported by an integrative approach combining phylogenomic, palynological, and morphological datasets. Neoschizaea is distinguished from all other genera by the combination of its linear, dimorphic fronds, large monolete spores (up to 105 µm) with coarsely reticulate and strongly perforate ornamentation, and a superficial, filamentous, and chlorophyllous gametophyte. We provide the new combination Neoschizaea pusilla, a formal description, and an updated identification key for the genera of Schizaeaceae.